2020
DOI: 10.1001/jamapediatrics.2019.4532
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adverse Hearing, Growth, and Discharge Age Outcomes With Postnatal Cytomegalovirus Infection in Infants With Very Low Birth Weight

Abstract: IMPORTANCE Studies suggest that postnatal cytomegalovirus (CMV) infection can lead to long-term morbidity in infants with very low birth weight (VLBW; <1500 g), including bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), and neurodevelopmental impairment. However, to date, the association of postnatal CMV with hearing, growth, and length of stay among VLBW infants is unknown.OBJECTIVES To determine the risk for failed hearing screen, increased postnatal age at discharge, or decreased growth at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 63 publications
4
83
0
Order By: Relevance
“…Another important recent study that may have major implications for our understanding of the neurodevelopmental consequences of pCMV infection was recently reported by Weimer and colleagues. 62 As noted, cCMV infection is well recognized to be a major cause of SNHL, 17 but this association had not been noted in the context of pCMV infection. 53 This group examined the prevalence of failed hearing screens, the calculated postnatal age, and somatic growth parameters at discharge in VLBW infants with pCMV infections (and uninfected controls) at the time of NICU discharge.…”
Section: Potential Long-term Neurodevelopmental Complications Of Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important recent study that may have major implications for our understanding of the neurodevelopmental consequences of pCMV infection was recently reported by Weimer and colleagues. 62 As noted, cCMV infection is well recognized to be a major cause of SNHL, 17 but this association had not been noted in the context of pCMV infection. 53 This group examined the prevalence of failed hearing screens, the calculated postnatal age, and somatic growth parameters at discharge in VLBW infants with pCMV infections (and uninfected controls) at the time of NICU discharge.…”
Section: Potential Long-term Neurodevelopmental Complications Of Pcmentioning
confidence: 99%
“…However, in the Weimer study, NEC did not stand out as a complication of pCMV infection, although an association between pCMV infection and BPD was confirmed. Weimer et al also observed that viral infection was associated with an increased postnatal age at discharge of nearly 12 days and a lower weight‐for‐age z‐score, suggesting that CMV infection prolonged hospitalization and had a negative impact on infant growth 62 . An impact of delayed hospital discharge on the overall cost of care was not investigated, but this issue should be examined in future cost–benefit analyses 66…”
Section: Breast Milk‐acquired Post‐natal CMV Infectionsmentioning
confidence: 99%
“…Short-term sequelae include hepatosplenomegaly, hepatitis, altered hematological parameters (neutropenia, lymphocytosis, thrombocytopenia), pneumonia, and sepsis-like syndrome (SLS) [ 11 , 18 , 19 ], followed by bronchopulmonary dysplasia (BPD) and/or necrotizing enterocolitis (NEC) [ 11 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Short- and Long-term Sequelae In Preterm Infants With CMVmentioning
confidence: 99%
“…A matched retrospective cohort study including a large number of VLBW infants from many neonatal intensive care units (NICUs) in the United States showed that post-natal CMV infection via breast milk statistically increased risks of death and BPD [ 21 ]. A multicenter cohort study showed that postnatal CMV infection in VLBW infants correlated with an 80% relative increase in the risk of having a failed hearing screen, increased postnatal age at discharge, lower weight at 40 weeks post menstrual age (PMA) and an increased risk of BPD, but not an augmented risk of NEC [ 22 ].…”
Section: Short- and Long-term Sequelae In Preterm Infants With CMVmentioning
confidence: 99%
“…Long-term neurological sequelae are observed in 16.8–18.8% of children with congenital CMV ( 5 ). Recently, it has also been suggested that post-natally acquired CMV infections can produced long-term neurodevelopmental sequelae in very-low-birthweight premature infants ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%